Latin America Climate- Smart Villages AR4D sites: 2020 Inventory - Bonilla Findji, Osana; Álvarez Toro, Patricia; Martínez Barón, Deissy; López, Claudia; Álvarez, Osman; Castellanos, Andrea; Martínez, Jesús David (2020)
Inventory of CSA practices evaluated and/or implemented across Latin America’s Climate-Smart Villages in 2020.